Institutional Dynamics and Economic Resilience in Central and Eastern EU Countries. Relevance for Policies - Gabriela Carmen Pascariu; Andreea Iacobuță-Mihăiță; Carmen Pintilescu; Ramona Țigănașu (Transylvanian Review of Administrative Sciences, 2021)
In the global context generated by the 2008-2009 economic crisis and by the current COVID-19 pandemic, the analysis of the way in which territories can resist, return and adapt to shocks has become a priority for resilience-based policies. The paper aims to investigate the role of institutions in economic resilience, in the particular case of Central and Eastern European countries since, despite the ongoing convergence process, the institutional gaps and weaknesses of these states challenge their possibilities to recover after this health crisis, as well as to improve their resilience capacity. The methodological approach involves, firstly, a cross-country time-series panel regression, using the annual data from 1996 until 2019. Secondly, we applied the principal component regression, in order to capture the country specificities. The research focuses on the linkages between institutional dynamics and economic resilience, an issue less reflected in literature. Our results confirm the influence of institutional factors on economic resilience and, more importantly, it is highlighted that the ‘one size fits all’ principle does not apply in the case of recovery and resilience programs, which is due to the fact that institutions act differently, depending on various socio-economic and political contexts.